2017
DOI: 10.1002/wnan.1455
|View full text |Cite
|
Sign up to set email alerts
|

Pioneering medical advances through nanofluidic implantable technologies

Abstract: Nanofluidic implantables represent a recent advance in a broad effort for developing personalized, point-of-care medical technologies. Such systems have unprecedented potential when matched with the newest developments in robotics, microprocessing, and tissue engineering. In this review, we present their emergence in medicine within the fields of diagnostics, biosensing, therapeutics, and theranostics. Discussion includes current limitations and future directions for these systems, as commensurate advances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 117 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…On another note, biomedical microelectromechanical systems/nanoelectromechanical systems (BioMEMS/BioNEMS) based micro-or nano-fluidics platforms encompassing either transdermal or implantable modalities are emerging approaches for local controlled release to confine drug to the tumor. [94][95][96] For example, iontophoresis is a non-invasive type of transdermal drug delivery that enhances penetration of charged molecules across the skin under an applied electric field. This technique is currently used in the clinic for pain management, hyperhidrosis (excessive sweating), with some research directed toward treatment of inflammatory conditions.…”
Section: Chemotherapymentioning
confidence: 99%
“…On another note, biomedical microelectromechanical systems/nanoelectromechanical systems (BioMEMS/BioNEMS) based micro-or nano-fluidics platforms encompassing either transdermal or implantable modalities are emerging approaches for local controlled release to confine drug to the tumor. [94][95][96] For example, iontophoresis is a non-invasive type of transdermal drug delivery that enhances penetration of charged molecules across the skin under an applied electric field. This technique is currently used in the clinic for pain management, hyperhidrosis (excessive sweating), with some research directed toward treatment of inflammatory conditions.…”
Section: Chemotherapymentioning
confidence: 99%
“…Personalized medicine approaches tailored to an Pharmaceutics 2023, 15, 1795 2 of 13 individual patient's genetic and phenotypic nuances are a shared vision across medicine. Although cervical cancer treatment is selected on a case-specific basis, new sustained drug delivery systems for treating a localized area are urgently needed to increase the survival rate for metastatic and/or recurrent cervical cancer in patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The simulated structure showed that the membranes would actuate, and that the stress due to actuation would not exceed the fracture stress of our materials. Since implantable devices for medical analysis and drug delivery is a particularly compelling motive for this type of miniaturization [14], we report now on the application of our structure as a pump.…”
Section: Introductionmentioning
confidence: 99%